The Socio-Economics Dynamics at Distribution of Small Scale Bananas Comodity in West Java - Vidiastuti Sholihah, Fasih; A. Kinseng, Rilus; Sunito, Satyawan (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2017)
ABSTRACTThe pattern of the commercial banana farm rise the socio-economic dynamics in the value chain banana distribution. In West Java, the exposure to market information make banana farmers get access to the market directly but they have to encounter a domination of big seller (Bandar). This study aimed to analize the types of value chain and the relationships among the actors. This research was conducted in Cugenang, Cianjur, West Java by using qualitative methods of case approach. The results showed seven types of value chain in the banana distribution among the farmers to the consumer which realization the cooperation relationship of information flow, production inputs, and finance. The chain was build based on kinship, relationship farmer groups, relationship capital, and direct access to the market. Farmers related to middlemen for sorting and packing bananas, while relations with Bandar done by middlemen in capital bond. Farmer groups member had relationship with marketers group (BPK) which do grading the quality of bananas. Relations with capital loans bonding between farmer-middleman-Bandar made value chain grew longer and farmers increasingly passive in determining the price. Competition occured between sections of middlemen at the local level because of the dominance Bandar who controlled the market access. BPK independently sell commodities had compete with Bandar who has a network of cooperation in the middleman.Keywords: actor, competition, coorperation, market, value chainABSTRAKPola pertanian pisang yang komersil memunculkan dinamika hubungan sosial-ekonomi dalam rantai nilai pendistribusian pisang. Di Jawa Barat, terbukanya informasi mengenai pasar membuat petani pisang mendapatkan akses langsung ke pasar namun masih terdapat dominasi penguasa modal besar. Penelitian ini bertujuan untuk mengidentifikasi jenis-jenis value chain (rantai nilai) dan relasi antar aktor pada sistem rantai nilai dalam pemasaran komoditas pisang. Penelitian ini menggunakan desain metode kualitatif yaitu studi kasus di Kecamatan Cugenang, Cianjur, Jawa Barat. Hasil penelitian menunjukkan terdapat tujuh tipe value chain pada distribusi pisang antara petani sampai ke konsumen akhir yang merupakan perwujudan relasi kerjasama aliran informasi, input produksi, dan keuangan. Rantai tersebut dibangun berdasarkan hubungan kekerabatan, hubungan kelompok tani, hubungan permodalan, dan akses langsung ke pasar. Petani berelasi dengan tengkulak dalam hal sortir dan packing, sedangkan relasi dengan Bandar dilakukan oleh tengkulak dengan ikatan modal. Kelompok tani yang masih aktif menjalin relasi dengan bagian pemasar kelompok (BPK) yang melakukan grading kualitas pisang. Relasi ikatan pinjaman modal antara petani-tengkulak-bandar menjadikan rantai nilai semakin panjang dan petani semakin pasif dalam menentukan harga. Persaingan terjadi antar bagian tengkulak pada tingkat lokal daerah karena dominasi akses pasar luar dikuasai oleh Bandar pisang. BPK yang menjual komoditasnya secara mandiri harus bersaing dengan dominasi Bandar yang memiliki jaringan kerjasama di tengkulak.Kata kunci: aktor, kerjasama, persaingan, relasi, value chain